Zinc induces normoxic accumulation of transcriptionally active hypoxia-inducible factor 1-alpha in mammary epithelial cells - Lee, S. Y.; Mustafa, S.; Ching, Y. W.; Shafee, Norazizah (Federation of European Biochemical Societies, 2017)
Both zinc and the α-subunit of hypoxia-inducible factor (HIF-1α) play important roles in the remodelling of mammary gland tissues. In the present study, we examined the level and the transcriptional activity of HIF-1α in mammary cells upon zinc treatment. In MCF-7 mammary adenocarcinoma and MCF-10A mammary epithelial cell lines, the toxicity levels of zinc differ. Interestingly, both cell lines overexpress HIF-1α following zinc treatment. As it was evident from an up-regulation of its specific target gene CA9 that encodes carbonic anhydrase IX, the stabilized HIF-1α translocated to the nucleus and was transcriptionally active. Hence, we conclude that zinc causes normoxic accumulation of transcriptionally active HIF-1α by interfering with its post-translational regulation.